Design of Low Power CMOS Bioamplifier in 250 nm and 90 nm Technology Node - Wan Jusoh, Wan Mohammad Ehsan Aiman bin; Ruslan, Siti Hawa; Che Soh, Mohd Jais (International Journal of Integrated Engineering, 2017)
The advancement of Complementary Metal Oxide Semiconductor (CMOS) technology has enabled a better design in bioamplifier for electroencephalography (EEG) and electrocardiogram (ECG) signals acquisition systems. Bioamplifier can be designed using two-stage CMOS operational transconductance amplifier (OTA). This paper presents the performance of CMOS bioamplifier which had been designed using two CMOS technology; one using 250 nm and the other in 90 nm technology. The 250 nm CMOS bioamplifier operates with ±2.5 V voltage supply and has open loop gain of 82 dB and the common mode rejection ratio (CMRR) of 92 dB, meanwhile the 90 nm CMOS bioamplifier operates with ±1.2 V voltage supply and has open loop gain of 72.9 dB and common mode rejection ratio (CMRR) of 73.03 dB. The power consumed by the OTA bioamplifier is 5.56 mW for the 250 nm amplifier and 15.53 µW for the 90 nm amplifier.